Case Report: Generalised Panniculitis as a Post-COVID-19 Presentation in Aicardi-Goutières Syndrome Treated With Ruxolitinib - Pararajasingam, Abirami; Bradley, Rachel E.; Evans, Jennifer; Lowe, Ashima; Goodwin, Richard; Jolles, Stephen (Frontiers in Pediatrics, 2022)
Aicardi-Goutières Syndrome (AGS) is a hereditary early-onset encephalopathy. First described in 1984, this rare disorder is characterized by upregulation of the type 1 interferon (IFN) pathway, which is involved in the host immune response against viral infections, including SARS-CoV-2. Whilst defects in type 1 IFN pathways have been described in association with severe Covid-19, little is known about the outcomes of upregulation, and we describe an unusual case of generalized panniculitis as a post-Covid-19 phenomenon in a child with AGS.